English Language & Linguistics (Cambridge)
English Language and Linguistics, published three times a year, is an international journal which focuses on the description of the English language within the framework of contemporary linguistics. The journal is concerned equally with the synchronic and the diachronic aspects of English language studies and publishes articles of the highest quality which make a substantial contribution to our understanding of the structure and development of the English language and which are informed by a knowledge and appreciation of linguistic theory.
Keywords: Language